Pengaruh Pengetahuan Keuangan, Sikap Keuangan dan Kepribadian terhadap Perilaku Manajemen Keuangan Padapelaku UMKM di Kecamatan Meureubo Kabupaten Aceh Barat - Ika Marlisa; Muzakir Muzakir (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the effect of financial knowledge, financial attitudes, and personality on financial management behavior in MSME actors in Meureubo District, West Aceh Regency. This study is a quantitative study. The sample intended in this study were MSME actors in Meureubo District as many as 84 people. This study uses primary data related to the identity of the respondents, as well as the perceptions of respondents regarding financial knowledge, financial attitudes, the influence of personality and financial management behavior. The analysis used in this study is multiple linear regression analysis (multiple regression). The results of this study indicate that partially 1) there is an influence of financial knowledge on the financial management behavior of MSME actors, 2) there is an influence of financial attitudes on the financial management behavior of MSME actors and 3) there is an influence of personality on the financial management behavior of MSME actors. Simultaneously, financial knowledge, financial attitudes, and personality have a significant effect on the financial management behavior of MSME actors in Meureubo District, West Aceh Regency, with the Fcount value (24.297) greater than Ftable (3.111) and the significance value is 0.000.